Różnice w wycenie opcji realnych metodą dwukrotnej symulacji Monte Carlo i z zastosowaniem formuły Blacka-Scholesa - Wiśniewski, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Paper examines concept of real option valuation method based on simulation approach. Monte Carlo (MC) simulation is proposed by Copeland and Antikarov to resolve the problem of many uncertainty factors influencing the project. In the next step typical option valuation techniques could be used - MC simulation being one of them. The proposal of the author is to simulate the expected value of the project in two models. In the first model one should calculate during simulation the base value of the project without option and in the second model one should calculate the expected value of the project with option executed. Mean difference between projects values set the value of the real option. The example of calculation is included and compared to valuation of the same case with Black-Scholes (BS) formula. Valuation with double MC methods results in value of real option lower than option value calculated with BS formula by 87%. Reasons of such differences could be: assumption of the geometric Brownian motion in BS, consolidation of risk proposed by Copeland Antikarov and interrelation among many different parameters which are not included in the MC model. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 497-506